OPEN GLOBE INJURIES WITH INTRAOCULAR FOREIGN BODY: SURGICAL OUTCOME - Hussain, Zakir; Khan, Sadique Ullah; Jan, Sanaullah; Shahnam, Tariq (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine surgical outcome and residual co-morbidities after surgical intervention in eyes having Open Globe Injury (OGI) with retained Intra Ocular Foreign Body (IOFB). Methodology: A prospective interventional case series was carried out at the department of Ophthalmology, Khyber Institute of Ophthalmic Medical Sci-ences (KIOMS), Hayatabad Medical Complex (HMC), Peshawar from 1st Sep-tember 2012 to 30th November 2013. Patients who were followed post-op -eratively for at least 90 days were included. Eyes having open globe injury (OGI) and intraocular foreign body (IOFB) who had surgical intervention were included in our study. Visual outcome was determined comparing final best corrected visual acuity (BCVA) with initial BCVA. Co-morbidities were noted at final follow up. For data analysis, Snellen's VA was converted to log MAR VA. Data was analyzed by SPSS version 16. Results: Total of 35 patients were included in our study. Male were 94.3% compared to 5.3% females. Mean age was 32.42 years. Bomb blast injury was cause of eye trauma in 60% cases while 40% were doing hammer and chisel work at the time of trauma. IOFB was impacted in anterior segment in 20% cases while it was impacted in posterior segment in 80% cases. IOFB remov-al was achieved in 33(94.28%) cases; silicone oil was used as temponade in 48.57% cases. Primary repair was required in 40% cases while rest 21(60%) eyes had self sealed wound. Primary surgical intervention in the form of Pars Plana Vitrectomy, IOFB removal with the use of intraocular magnet or forceps was carried out in 71% cases. Mean BCVA log MAR improved from initial BCVA of 2.20 to 1.20. Common comorbidities at final visit were corneal scars, macular scars and cataract. Conclusion: Bomb blast injuries are most common cause of OGI with IOFB in our region. Significant visual improvement occurs in most of the cases after skilled vitreo-retinal surgical interventions. Common ocular co-morbidities are corneal scar, macular scar and cataract.